Solution and solid-state Excited-State Intramolecular Proton Transfer (ESIPT) emitters incorporating Bis-triethyl-or triphenylsilylethynyl units. (January 2019) - Massue, Julien; Felouat, Abdellah; Curtil, Mathieu; Vérité, Pauline M.; Jacquemin, Denis; Ulrich, Gilles
Abstract: Excited-State Intramolecular Proton Transfer (ESIPT) emitters based on a 2-(2′-hydroxyphenyl)benzazole (HBX) scaffold, incorporating triethyl- or triphenylsilyl substituents either at the 3′, 5′ positions of the benzoxazole ring or at the 3, 5 positions of the phenol cycle have been synthesized through an expedite two-steps synthetic route. Upon excitation and depending on the substitution and environment, these fluorophores display either single (keto) or dual (enol/keto) fluorescence emission spanning from 400 to 570 nm. Unlike the majority of reported ESIPT emitters, these rigidified dyes display intense fluorescence intensity in the solution-state in either aprotic apolar (toluene) or protic polar (ethanol) solvents with observed emission quantum yields (QY) up to 52% and 44%, respectively. These values represent a drastic enhancement as compared to unsubstituted HBX dyes which feature QY between 1 and 2% in toluene. These fluorophores remain highly emissive in the solid-state, as dispersed in KBr pellets or doped in PMMA films (QY up to 77% and 60% respectively). Molecular engineering studies showed that it is possible to fine-tune the emission color with very small modifications of the HBX scaffold. The nature of the excited-states was also probed through ab initio calculations, evidencing in each case a transition from the K ∗ state. Graphical abstract: Image 1 Highlights: Six original emitters displaying Excited-State Intramolecular Proton Transfer (ESIPT) emission are presented. Their full photophysical characterization in solution and in the solid-state is described. Ab initio calculations were performed to modelize the excited-states.